Alkalinity Production Coupled to Pyrite Formation Represents an Unaccounted Blue Carbon Sink. Issue 4 (8th April 2021) - Reithmaier, Gloria M. S.; Johnston, Scott G.; Junginger, Tobias; Goddard, Madeline M.; Sanders, Christian J.; Hutley, Lindsay B.; Ho, David T.; Maher, Damien T.
Abstract: Blue carbon ecosystems, including mangroves, saltmarshes, and seagrasses, mitigate climate change by storing atmospheric carbon. Previous blue carbon research has focused on organic carbon stocks. However, recent studies suggest that lateral inorganic carbon export might be equally important. Lateral export is a long‐term carbon sink if carbon is exported as alkalinity (TAlk) produced via sulfate reduction coupled to pyrite formation. This study evaluates drivers of pyrite formation in blue carbon ecosystems, compares pyrite production to TAlk outwelling rates, and estimates global pyrite stocks in mangroves. We quantified pyrite stocks in mangroves, saltmarshes, and seagrasses along a latitudinal gradient on the Australian East Coast, including a mangrove dieback area, and in the Everglades (Florida, USA). Our results indicate that pyrite stocks were driven by a combination of biomass, tidal amplitude, sediment organic carbon, sediment accumulation rates, rainfall, latitude, temperature, and iron availability. Pyrite stocks were three‐times higher in mangroves (103 ± 61 Mg/ha) than in saltmarshes (30 ± 30 Mg/ha) and seagrasses (32 ± 1 Mg/ha). Mangrove pyrite stocks were linearly correlated to TAlk export at sites where sulfate reduction was the dominant TAlk producing process. However, pyrite generation could not explain all TAlk outwelling. We present the first global model estimating pyrite stocks in mangroves, giving a first‐order estimate of 197 Mg/ha (RMSE = 24 Mg/ha). In mangroves, estimated global TAlk production coupled to pyrite formation (∼3 mol/m 2 /y) is equal to ∼24% of their global carbon burial rate, highlighting the importance of including TAlk export in future blue carbon budgets. Plain Language Summary: Mangroves, saltmarshes, and seagrasses (known as blue carbon ecosystems) have the potential to buffer climate change by taking up carbon dioxide. Scientists assess this potential by measuring the amount of carbon that is stored in the soils of these ecosystems. However, soil carbon is partly broken down by microorganisms and can be exported to the coastal ocean. Carbon export to the coastal ocean is also a carbon sink. The prerequisite, however, is that carbon breakdown is coupled to the formation of iron sulfide minerals (i.e., pyrite), which prevents reactions that would lead to carbon dioxide release. This study examined the driving factors and global importance of iron sulfide mineral formation and related carbon export in blue carbon ecosystems. We found that biological, climatic, and geological factors impact iron sulfide mineral formation. We used these findings to develop the first global model predicting iron sulfide mineral reserves in mangroves. Our results show that the dissolved carbon produced during sulfide mineral formation corresponds to a quarter of the carbon stored in mangrove soils. This study highlights the importance of considering dissolved carbon export when evaluating the potential of blue carbon ecosystems for mitigating climate change. Key Points: Alkalinity export from blue carbon ecosystems is a long‐term carbon sink if alkalinity production is coupled to pyrite formation We present the first global model for pyrite stocks in mangroves, estimating that mangrove pyrite stocks average around 197 Mg/ha Globally, pyrite formation in mangroves produces 0.45–0.68 Tmol alkalinity per year, making the process a substantial carbon sink